1999
DOI: 10.1038/sj.bmt.1701755
|View full text |Cite
|
Sign up to set email alerts
|

Expression of T cell activation antigen CD134 (OX40) has no predictive value for the occurrence or response to therapy of acute graft-versus-host disease in partial T cell-depleted bone marrow transplantation

Abstract: Summary:CD134 (OX40) is a member of the tumor necrosis factor family which is expressed by activated T lymphocytes. CD134 expression on T cells was monitored during the first 35 days post-transplant in 14 patients, receiving either an HLA-identical sibling bone marrow transplant (BMT), a matched unrelated transplant (MUD-BMT) or an autologous peripheral blood progenitor cell transplant (PBPCT). The sibling and unrelated grafts were partially depleted of T cells. CD134 expression on CD4 + T cells peaked between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In contrast, previous studies showed that monitoring OX40 ϩ T cells was not useful for the prediction of aGVHD. 17 We assume that the pathogenesis of aGVHD and cGVHD may not be identical 2 and infections that are more common within 100 days after allo-HSCT 18 might modify the expression of OX40.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, previous studies showed that monitoring OX40 ϩ T cells was not useful for the prediction of aGVHD. 17 We assume that the pathogenesis of aGVHD and cGVHD may not be identical 2 and infections that are more common within 100 days after allo-HSCT 18 might modify the expression of OX40.…”
Section: Resultsmentioning
confidence: 99%
“…Several but not all studies in humans have suggested that OX40 up-regulation can precede acute GVHD generation and may be a marker of steroid-resistant acute GVHD or chronic GVHD. [44][45][46][47] Regardless of whether the upregulation of OX40 receptor is of prognostic significance, interruption of the OX40/OX40L pathway early in the post-BMT period warrants testing as an approach to prevent GVHD and allogeneic BM graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism for the protective effect of IVIg is of particular interest since, in a similar parent into F1 animals model of aGVHD, the presence of CD4 + CD134 + T cells was suggested to be associated with the onset and clinical course of aGVHD [23]. Furthermore, CD4 + CD134 + T cells recovered from methylprednisolone-treated patients with GVHD were documented as being resistant to apoptosis [24].…”
Section: Discussionmentioning
confidence: 99%